Uncoupling the exploitation and climate change effects on the biology of Cape monkfish, Lophius vomerinus Valenciennes 1837 in Namibia - Erasmus, Victoria Ndinelago (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science)
Cape monkfish, Lophius vomerinus Valenciennes 1837, has supported the Namibian fishing industry for decades, historically as by-catch and recently as a target species. This species is also an important predator in this region. With increasing levels of exploitation and unprecedented climate change, an understanding of the changes in the long-term biological parameters of this species is critical. To date, there has been a scarcity of spatio-temporal studies that have examined and compared the biological aspects of Cape monkfish in relation to climate change and exploitation pressure. Investigations into changes in feeding habits, reproduction strategy, age and growth can provide valuable information for the sustainable management and conservation of this species. This thesis aimed to improve our understanding of the impacts of exploitation and climate variability on the biological parameters of Cape monkfish in the Namibian marine waters, thereby contributing to efforts directed at sustainable harvest and management of this resource. This was achieved through temporal and spatial comparisons of feeding, reproductive scope, age and growth, and catch statistics. The study used data collected during the monkfish swept-area biomass surveys of 2001"“2005 and for 2007"“2018, hake (deep-water hake Merluccius paradoxus Franca 1960 and shallow-water hake M. capensis Castelnau 1861) swept-area biomass surveys of 2017 and 2019, port sampling programme data collected from April 2014 to December 2019, and monkfish commercial fishing activities collected between April 2001 and December 2019. Based on historical feeding data (1986 "“ 1987) and contemporary feeding data (2015-2018), Cape monkfish feeds on a variety of prey species from seven groups: Teleost, Cephalopoda, Crustacea, Echinoidea, Elasmobranchii, Gastropod and Porifera. The diet was characterised by a high prevalence of empty stomachs (43.9%), showing low feeding intensity, but most prevalent in juveniles (52.9%). Although the diet composition varied at different life stages, Teleosts (especially deep-water hake Merluccius paradoxus Franca 1960) were the main constituents of the diet for all size classes as per the Index of Relative Importance (%IRI). The results highlight the particular importance of the deep-water hake M. paradoxus (by %IRI) in the diet of Cape monkfish across all size classes. There is a clear dominance of hake in both studies, which means that any overexploitation or climate-driven population decline in hake will most likely have an impact on Cape monkfish. Feeding composition was dependent on the season (p < 0.05), with the type and quantity of prey ingested changing seasonally, showing the ability of Cape monkfish to adjust its diet, depending on possible environmental parameters which consequently influence prey availability. In general, the spatial and temporal variability of the main prey items suggests that the species is highly opportunistic with a broad trophic adaptability. Comparison of historical and contemporary stomach content data indicates that Cape monkfish appear to have changed their diet, probably reflecting the availability of forage species over time and space, possibly due to climate change, fishing pressure, or both. The broad trophic adaptability for Cape monkfish highlights their adaptive potential to increasing anthropogenic stressors such as climate change. However, the dominance of the commercially important deep-water hake, M. paradoxus, in the diet during contemporary times highlights that complex trophic interactions may play a role in altering the northern Benguela fisheries. The general male to female sex ratio was measured at 1:1.67, with significant variation across depth, size class, and year (p < 0.05). Comparison of length at 50% maturity (L50) for Cape monkfish between historical (2004"“2006) and contemporary time (2015"“2019) showed no significant differences in both sexes, with no significant changes in the L50 for females (Ï‡2 = 1.53, df = 1, p = 0.2154), and males (Ï‡2 = 0.41, df = 1, p = 0.5204) between the two periods. The monthly gonadosomatic index (GSI) showed that Cape monkfish spawn throughout the year with peaks between July and September for females and August for males, similar to those observed 20 years ago. Spawning hotspot areas were identified and were consistently located between 22â ° and 25â °S in deeper water (> 250 m) for the 2001"“2018 time series. Comparison of the contemporary (2015"“2019) proportions of developing, ripe and spent gonads to the historical study data (1996 "“ 2000) show minimal differences. Ripe ovaries capable of spawning (Stage IV) were dominant in July (23.8%) and August (26.2%), while ripe testes were prevalent in April (52.5%) and November (28.5%). The discovery of the veil (a gelatinous, flat ribbon structure containing individual eggs) off Namibia for the first time (during this study) is a significant because this result provides important reproduction activities information of this species, which were never recorded off Namibia. The location where the veil was discovered, off Swakopmund (22â °30'S, 13â °25'E), provides further evidence of the identified spawning hotspot areas, this location is also identified as a monkfish consecutive hotspot fishing area. The ages, growth rates, and length-weight relationships were compared between fish collected during monkfish commercial fishing activities between 1996 and 1998 (Period 1) and during monkfish routine monitoring surveys from 2014 to 2016 (Period 2). A total of 607 (size range: 9"“96 cm total length (TL)) and 852 (size range: 9"“96 cm TL) Cape monkfish were aged by reading sectioned illicia, during Periods 1 and 2, respectively. The length-weight relationships were W = 0.012L3.035 (r2 = 0.98) and W = 0.014L 2.989 (r2 = 0.98) for females and males, respectively, during Period 1, and W = 0.01L2.97 (r2 = 0.98) and W = 0.01L 3.03 (r2 = 0.98) for females and males, respectively, in Period 2. The growth of Cape monkfish (in cm) for combined sexes was described by Lt = 94(1 âˆ’ e(âˆ’0.10(tâˆ’(-0.31))) in Period 1 and Lt = 98(1 âˆ’ e(âˆ’0.10(tâˆ’(-0.33))) in Period 2. Females grew significantly faster during Period 1 (LRT results from Maartens et al., 1999), while male and female growth was not significantly different during Period 2 (F = 0.65, p = 0.58). There were no significant differences between the male and female growth curve in Period 2 (F = 0.65, p = 0.58). Although the growth curves are similar between Period 1 and Period 2, the larger fish are in Period 2 are lighter than those in Period 1. This finding is important to the monkfish fishing industry because fish is sold by weight. This finding may suggest that although the fish grow similarly by length, changes in the environmental conditions may have resulted in a reduced condition of the fish. In terms of mean age, the historical Period 1 had a slightly lower mean age of 4.40 compared with a mean age of 5.49 during Period 2. Slight differences were also observed in the age structure between the two periods, with 2-year-olds (20.3%) the most abundant age class in the historical period while 5-year-old fish (18.3%) were most abundant in Period 2. Although the spatial distribution of the catch was not available for Period 1, 0-year-old fish were distributed from 22â ° to 24â °S, and 25â ° to 26â °S in shallower waters of 166"“290 m during Period 2. Only fish between 5 and 16 years old were found off the documented historical nursery area off 28Âº S. The similar growth curves and spatial overlap of nursery habitats between Period 1 and Period 2 suggest that Cape monkfish may be fairly resilient to the rapid environmental change reported in this region and to the extensive levels of exploitation for the species. However, the recent spatial shifts in the nursery areas are sensitive to disturbance and may indicate that these changes could be having an impact on the early life stages of the species. Continued monitoring may be necessary to understand the consequences of these spatial shifts for the age and growth and resilience of the species. Analysis of the overall spatial and temporal catches of monkfish (both Cape monkfish and shortspine African monkfish) off Namibia between 1998 and 2018 identified noticeable spatio-temporal trends. The pattern of fishing activities for Cape monkfish is heterogeneous, with identified "˜hotspots"™ in specific areas. Of particular importance is the consecutive hotspot, between 1998 to 2018 for monkfish fishing activities between 25â ° and 26â ° S. The kernel density analysis indicated that the area around 24â °S, and between 26Âº and 27 â °S, between Walvis Bay and LÃ¼deritz, had the highest total catch densities (~300 kg/km2), suggesting that this is the core of the stock abundance. Annual monkfish catches have fluctuated since the inception of the fishery in 1994, with a drastic decline in the catch recorded after 2003 through to 2018. Generally, there has been an underutilisation of the total allowable catch (TAC) for most of the years. The decrease in catches and the underutilisation of the TAC might be indicative of the reduction in the stock abundance. However, external factors such as lack of capacity of the fishing industry and the administration can contribute to underutilisation of TAC. Basic regression analysis between total monthly catches and monthly sea surface temperature (SST) yielded low r-squared values indicate that in all three grids, only ~ 1% of the variation is explained between SST and total monkfish catches in these areas. The most prominent points to consider from this study are the results of the comparative feeding study (Chapter 3), reproductive indicators (Chapter 4) and age and growth (Chapter 5). Certainly, there have been changes in feeding, demography, and distribution of the species in the last two decades "“ climate-driven changes were recorded in the feeding habits of Cape monkfish, spatially and temporally "“ but despite the changes in prey species composition, distribution and abundance in various habits and periods, Cape monkfish was able to switch prey species, reflecting wide trophic adaptability. The dominance of M. paradoxus at all size classes in all analysed habitats is a significant result because. The peak spawning period has remained the same between July and September, as previously reported in Period 1. The consecutive spawning hotspots were identified in the areas between 22Âº and 25ÂºS. From a fisheries management perspective, the spawning ground and spawning season should be protected (by means of closure). The evidence of changes in length at 50% maturity presented in this study hints at both climate change and extensive exploitation pressure. The discovery of the veil for the first time in this study is very important; however, it might be sampling related and not driven by climate or exploitation pressure. Finally, the change in the Cape monkfish distribution discussed in Chapter 6 may be attributed to a shift in the distribution or fishing effort as a consequence of shallow water depletion.,Thesis (PhD) -- Faculty of Science, Ichthyology and Fisheries Science, 2021
Keywords: Lophius-- Namibia; Lophius Climatic factors-- Namibia; Lophius Effect of human beings on-- Namibia; Lophius Food-- Namibia; Lophius Reproduction-- Namibia; Lophius Age-- Namibia; Lophius Growth-- Namibia; Lophius Habitat-- Namibia; Lophius Conservation-- Namibia; Fisheries-- Namibia; Overfishing-- Namibia; Fishery management-- Namibia; Lophius vomerinus (Valenciennes, 1837); Cape monkfish